Mindfulness and the relation with stress, affect and burnout in elite junior athletes - Davis, P.; Gustafsson, H.; Skoog, T.; Kenttä, G.; Harbel, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Burnout in sport has been considered as a maladaptive consequence of chronic stress and suggested to be associated with ill-health, poor performance, and ultimately dropout. A prospective treatment that has been forwarded as a preventative method to effectively manage the everyday stress of ambitious athletes is mindfulness. Therefore, the aim of the present study is to examine the relationship between mindfulness and burnout and whether this relationship is mediated by stress, negative affect and positive affect in elite junior athletes. Methods: Two hundred thirty six (136 males and 100 females) competitive elite junior athletes, (Mage = 17.4 years; SD = 1.08) completed the Mindful Attention Awareness Scale (Hansen et al., 2009), Athlete Burnout Questionnaire (Raedeke & Smith, 2001), Perceived Stress Scale (Cohen, et al., 1983), and Positive and Negative Affect Scale (Watson, et al., 1988). Results: The results reveled that mindfulness had a significant negative relationship with both stress and burnout. Mediation analyses indicated that positive affect fully mediated the links between mindfulness and sport devaluation, and that positive affect and negative affect partially mediated the relationship with physical/emotional exhaustion and reduced sense of accomplishment. Discussion: The results support mindfulness as negatively related to burnout in athletes and the influential role of positive affect. Future research should further investigate the unique variance in the relationship between mindfulness and burnout not explained by negative affect and perceived stress. Strategies to enhance athletes` mindfulness may be useful to prevent burnout and enhance performance.